Morphology and use of the bandicoot (Echymipera kalubu) by the Wamesa Tribe in Teluk Wondama Regency - Abutalib, Nurhaidah; Ranti, Febriza Dwi; Krey, Keliopas (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2025)
This research aims to identify the type of mole, its morphology, and the ethnobiology of bandicoots by the Wamesa Tribe in Teluk Wondama Regency. This research method is a descriptive method with observation and interview techniques. Research variables include morphology and ethnobiology of bandicoots. The research results show that the bandicoots used by the Wamesa Tribe are white-breasted and red-breasted E. kalubu. The hair's characteristics are spiky, short snout, tail length <100 mm, black areas on the eyes, and ears rounder. Based on the measurements of male and inner E.kalubu, they have a body weight of 1,600 vs 2000 g. hind leg length 411.7 vs. 414 mm, tail length 62.2 vs. 65 mm, hind foot length 57.8 vs. 54.5 mm, ear length 33.8 vs. 32.5 mm. The Wamesa tribe uses moles for consumption, cooked by stirring-frying using burning coals and natural kitchen spices, and the body part of the bandicoot is meat.